PROFIL BERPIKIR LATERAL SISWA DALAM PEMECAHAN MASALAH GEOMETRI DITINJAU DARI TAHAP BERPIKIR VAN HIELE - Restu Ria Wantika; Eka Susilowati (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2018)
The purpose of this study was to describe the lateral thinking of students in solving geometry problems reviewed by the van Hiele thinking stage. Humans have thoughts on things, especially mathematics emphasizing logical thinking, so one of the most suitable ways of thinking is lateral thinking. One of the things that can train lateral thinking is to solve problems. Geometry is a subject of mathematics that can support to know the lateral thinking of students because it trains students to think creatively to find alternative options to solve problems. This type of research is qualitative research. The research subjects were three junior high school students in grade VIII. Subjects were selected based on VGHT test results. Data collection methods used are observation during learning, tests and in-depth interviews. Research instruments are diagnostic tests and interview guidelines. Data analysis in this study is qualitative descriptive analysis. The data analyzed were observation data during learning, test results and the results of in-depth interviews which were used to describe the students' lateral thinking process in geometry problem solving